CONTROLLERSHIP: A STUDY OF ARTICLES PUBLISHED IN BIBLIOMETRIC EVALUATED BY PERIODIC CAPES - Melo, Dialison Luiz Silva de; Silva, Ana Paula Ferreira da; Falk, James Anthony; Nascimento, Rosemberg Gomes (RC&C. Revista de Contabilidade e Controladoria, 2013)
This study aimed to analyze, through articles published in leading accounting journals evaluated by CAPES, the research published on controllership in Brazil. The methodology utilized was exploratory and descriptive, with bibliometric and quantitative analysis. Thirty-five (35) articles were found that contain the word "controller" in the title as a result of the 14 journals analyzed. The findings of the survey revealed that: (1) of the journals analyzed, the Journal of Accounting & Finance of USP showed the highest rate of publication (28.6%); (2) most authors have academic training in management, with 59 (23, 9%) of the authors, from the 247 titles analyzed, demonstrating some level of training in controlling; (3) 91.4% of the articles were written in collaboration with other authors. In the references, different types of documents were used, especially books (62,3%), where the most cited was Controllership: an approach to economic management - GECON authored by Armando Catelli. Keywords: Controllership. Bibliometrics. Scientific production. Journal.